Weight Regain and Insufficient Weight Loss After Bariatric Surgery: Definitions, Prevalence, Mechanisms, Predictors, Prevention and Management Strategies, and Knowledge Gaps—a Scoping Review - Walid El Ansari (93732) (2022)
Some patients experience weight regain (WR) or insufficient weight loss (IWL) after bariatric surgery (BS). We undertook a scoping review of WR and IWL after BS. We searched electronic databases for studies addressing the definitions, prevalence, mechanisms, clinical significance, preoperative predictors, and preventive and treatment approaches including behavioral, pharmacological, and surgical management strategies of WR and IWL. Many definitions exist for WR, less so for IWL, resulting in inconsistencies in the reported prevalence of these two conditions. Mechanisms and preoperative predictors contributing to WR are complex and multifactorial. A range of the current knowledge gaps are identified and questions that need to be addressed are outlined. Therefore, there is an urgent need to address these knowledge gaps for a better evidence base that would guide patient counseling, selection, and lead to improved outcomes. Other Information Published in: Obesity Surgery License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s11695-020-05160-5